(untitled) (Revista Apotheke, 2019)
This work is an invitation to the reader to think together the hip-hop cultural movement as a contemporary art and tool of teaching and social transformation and the creative processes of rap construction and the concepts that surround their constructions, along with their possible displacement to field of education. It is in this context that the concept that surrounds the Rhymer-Educator-Reseacher act is presented articulating the rhymer - one who creates music, improvises, verses and poems, transmits the message and also receives it - the educator - the one who teaches and learns in a joint way, uses the scientific and empirical pedagogy - and the researcher - the one who uses his experience, goes to the field seeks to give depth to his knowledge, investigates, searches and collects data through readings, interviews, and other techniques to get what you need. In this sense, the Rhymer-Educator-Researcher articulates through the hyphen.